(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This research aimed to study the current and desirable conditions of teaching and learning supervision, develop a teaching and learning supervision model, and evaluate the results by experimenting with the Bachelor of Education in the Dancing Art Program. The research was divided into three phases: studying the current and desirable conditions, developing the model, and evaluating the results. The target groups included information providers, experts in the field of Thai dance arts, model experts, instructors in charge of the curriculum, and students in the field of dance art. The tools used included questionnaires, interview forms, group conversations, and record and evaluation forms. The results revealed that the study of current and desirable teaching and learning supervision conditions was at a moderate level of practice. In contrast, the desirable condition was at the highest level. The developed model had five main components: principles of patterns, the purpose of the model, teaching and learning supervision process with five steps, measurement and evaluation of model development, and success conditions. The evaluation results showed that the instructors who received supervision had higher knowledge and understanding of teaching and learning in dance art than before supervision. The supervised instructors could teach dance art according to the developed model with 87.79% and 87% efficiency in the teaching process and results, respectively. The effectiveness of teaching and learning using this model was 76% higher. The instructors who received supervision and students were satisfied with the teaching and learning supervision model at the highest level. Finally, the evaluation results for using the supervision model for teaching and learning management were at the highest level.